Altruism and peer-led hiv prevention targeting heroin and cocaine users - Convey, M.; Dickson-Gomez, J.; Weeks, M.; Li, Jianghong (Sage Publications, 2010)
Peer-delivered hiv prevention and intervention programs play an important role in halting the spread of hiv. rigorous scientific analysis of the aforementioned programs has focused on the immediate reduction of risk-related behaviors among the target populations. in our longitudinal study of the risk avoidance partnership peer intervention for hiv, we assessed the long-term behavioral effects of a peer-led hiv intervention project with active drug users. initial analysis of the qualitative data highlights the role of altruism as a motivator in sustaining peer educators beyond the immediate goals of the project. we contend that altruism found in volunteers is an important factor in maintaining long-term participation in hiv intervention programs and initiatives using peer educators. © the author(s) 2010.